Natural killer cell recognition of target cells expressing different antigens of vesicular stomatitis virus. - Moller, J R (1985)
Natural killer (NK) cells have the capability of lysing virus-infected, transformed, and embryonal cells, yet the nature of the target structure(s) recognized remains unclear. The availability of well-characterized temperature-sensitive (ts) mutants of vesicular stomatitis virus, defective in expression of individual viral-encoded polypeptides at the nonpermissive temperature (39 degrees C), offered an approach to elucidating NK-cell recognition of virus-infected cells. Target cells were infected with ts mutants in three functions: the viral surface glycoprotein (G protein; ts 045); the matrix (M) protein (ts G31, ts G33), and the polymerase (ts G11). Cells infected with wild-type virus and all ts mutants at the permissive temperature (31 degrees C) were killed by murine spleen cells. Similar to results on cytotoxic T lymphocytes, target cells infected by ts 045 defective in expression of G protein at 39 degrees C were not killed by NK cells. Unexpectedly, cells infected at 39 degrees C with the M-protein mutants also were not killed, although G protein was expressed at the cell surface. Target binding studies indicated that conjugates were not formed by cells infected with the ts mutants at the nonpermissive temperature. That expression of G protein was not sufficient for NK cell-mediated cytotoxicity was established in experiments in which a plasmid (pSVGL) containing the gene for vesicular stomatitis virus G protein was transfected into COS cells. Although G antigen was expressed on the plasma membrane, the cells were not lysed. These results suggest either that recognition of virus-infected cells depends on an appropriate conformation imparted to the viral G protein by association with the M protein or that NK cells can recognize alterations in the structure of the cell membrane induced by insertion of viral M and G molecules.